Roma children in the transformational recession - Widening ethnic schooling gap and Roma poverty in post-communist Hungary - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2005)
The Roma or "Gypsies" are Europe's largest and poorest ethnic minority. Nearly 80 per cent of them live in the former communist countries of Central and Eastern Europe. The Roma - Non-Roma educational gap, always substantial but slowly closing in the communist years, widened again after the collapse of the communist system in Hungary. Using Hungarian Roma data from the mid-1990's and a comparable national sample, we estimate multinomial probability models for dropping out after primary school (8th grade), continuing in vocational training school, or continuing in a secondary school with a maturity examination (necessary for college entrance). Our results indicate that long-term poverty of the Roma is strongly associated with their high drop-out rate after 8th grade. Roma poverty has increased considerably with the massive layoffs of unskilled workers since the mid-1980's. We find that the younger a child is when his/her father is laid off the more likely he/she is to discontinue schooling after 8th grade. We conclude that the collapse of Roma employment has been in part responsible for the widening ethnic gap in education. Equal opportunities for the next Roma generation are therefore jeopardized unless policy helps overcoming the adverse effects of long-term poverty on schooling outcomes.
Keywords: J15; I20; I30; 330; Roma minority; education; poverty; Hungary; Systemtransformation; Konjunktur; Ethnische Gruppe; Roma-Bevölkerung; Kinder; Bildungsniveau; Armut; Schätzung; Ungarn